Promoting Gender Parity Lessons From Yemen : A Jica Technical Cooperation Project in Basic Education - Yuki, Takako (Washington, DC: World Bank, 2012)
Despite remarkable progress supported by international commitment to meeting the MDGs, countries such as Yemen still face great challenges in achieving gender parity in education and in reducing in-country disparities. Strengthening community participatory school management is a key area which JICA has prioritized in its programs for reaching marginalized children and for improving access to and quality of education. One instance of this is a technical cooperation project in Yemen called Broadening Regional Initiative for Developing Girls Education (BRIDGE) Phase 1 (2005-2008), which piloted a participatory school management model supported by school grants with the objective of eliminating gender disparity in basic education. How successfully has this approach been in such a traditional society? Our analyses of the performance of the project's pilot schools based on analyses of data collected at three points in time - at the initial year and end year of the project and two years after the project's end - suggests the following: Interventions in school management that strongly emphasize girls can be effective in rather quickly improving gender parity regardless of the schools' initial conditions. However, we also observe that the post-project performance of the pilot schools in terms of gender parity is mixed, even though budgets for school grants were allocated by the local government to all pilot schools. We further observe that such variation in performance appears to be significantly correlated to school leaders' perceptions of gender equality, to community participation, and to the number of female teachers employed. These findings point to the importance of continuous long-term guidance to the schools and monitoring of those which implement school improvement programs. Attention should be paid to key factors that might influence school performance, such as those identified in this paper.